Pengaruh Volume Inokulum Acetobacter Aceti Dan Waktu Fermentasi Terhadap Fermentasi Asam Asetat Dari Nira Aren (Arenga Pinnata) - Yasminto, Habib Maulana; Chairul, Chairul; Utami, Syelvia Putri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sugar palm sap produced by sugar palm tree (Arenga pinnata). The sap is important product due to its sugar content can be used to produce brown sugar or fermented to ethanol and acetic acid. The sugar palm which is obtained from not fruit bunches with high sugar concentrations so as to provide an opportunity in the utilization of sugar palm to be acetic acid. Acetic acid can be produced naturally from ingredients containing sugar through fermentation using bacteria. The purpose of this study was to determine the result of ethanol in fermentation alcoholization, determine the effect of variations in the time of fermentation, variations in the volume of acetobacter aceti inoculum, determine the best acetic acid fermentation time for the concentration acetic acid obtained and determine the remaining ethanol and sugar during the asetification fermentation process. The bioethanol fermentation time is 6 day with volume of inoculum is 10% while the volume inoculum asetification fermentation 15% and the time of acetic acid fermentation is 16 day. The results of the analysis using the Nelson-Somogyi reagent revealed that the initial sugar concentration was 143.33 g/L. The maximum concentration of acetic acid obtained was 3.74%. This maximum concentration was obtained on 8 days of acetic acid fermentation at 15% of acetobacter aceti.Keywords : acetobacter aceti, acetic acid, fermentation, inoculum, sugar palm